“... And Their Mosques From Churches of God to Build in Distant Places”: to Qquestion of Formation of Interethnic and Interfaith Borders in Western Siberia in 18th Century - Z. A. Tychinskikh; S. R. Muratova (Научный диалог)
The process of building ethno-religious boundaries in the 18th century in the social space of Western Siberia is considered on the example of the provincial center — Tobolsk. The relevance of the study is due to the transformation of ethno-confessionalism from a cultural phenomenon into an instrument that can be used for political purposes in modern Russia. One of the methodological research tools is the method of analysis of the “new local history”, which allows you to create a holistic perception of the study of the social life of the past “at a local object”. The main stages of the state ethno-confessional policy in the 18th century are highlighted. The facts of the forced Christianization of Muslims are clarified. The authors draw attention to the role of the personal (subjective) factor in the processes under study. On the example of the activities of Metropolitan Sylvester Glovatsky and the governor F. I. Soimonov, the vector of the development of interfaith relations is considered, which often depends on the foresight and ideological attitudes of local authorities. Particular attention is paid to government decrees reflecting the position of the state in the ethno-religious sphere. The features are revealed and the main stages of the process of Christianization of Siberian Muslims during the 18th century are highlighted. The process of formation of interfaith boundaries in the multiethnic Siberian region is analyzed. The historiography of the topic under study is presented.